Academic motivation, procrastination, and adjustment: Exploring their impact on student profiles and academic performance - Patra Vlachopanou; Laura Maska; Dimitrios Kalamaras; Fani Nasika (PLoS ONE, 2025)
Introduction Succeeding in entering higher education studies is influenced by motivation, procrastination, and how well students adjust to university life. By understanding these factors, better strategies for supporting students can be developed. Aim This study aims to group university students based on their motivation, procrastination, and adjustment to university, and to examine how these groups relate to their Grade Point Average (GPA). Method 284 university students participated in this study, averaging 21.2 years old, of whome 36.2% were male and 63.4% female. Academic motivation was measured using the Academic Motivation Scale, procrastination with the Procrastination Assessment Scale Questionnaire, and adaptation with the Student Adaptation to College Questionnaire. A K-Mean cluster analysis and decision tree methods were used to identify student profiles and their link to GPA. Results Three profiles emerged: (a) Highly Motivated and Well-Adjusted (highest GPAs), (b) Moderately Motivated and Adjusted (average GPAs), and (c) Procrastinated and Poorly Adjusted (lowest GPAs). Conclusion Managing procrastination, staying motivated, and adjusting well to university are key to academic success. Targeted interventions can improve these areas and boost student performance.